(untitled) (Development Service Industry Management, 2025)
The article reveals the essence, content, and significance of integration mechanisms for the development and concentration of production capital of agricultural enterprises in the context of the transformation of the Ukrainian economy. It is substantiated that integration is an effective way to consolidate resources and achieve synergies, thereby increasing productivity, reducing costs, and strengthening market competitiveness. The primary forms of integration – vertical, horizontal, cluster, cooperative, and conglomerate – are analyzed, and their impact on the development of agricultural production is determined. It is shown that the process of capital concentration, particularly through mergers and acquisitions (M&A), contributes to the creation of powerful agricultural structures capable of attracting investment, introducing innovations, and implementing sustainable development strategies. Particular attention is paid to modern challenges, including institutional instability, limited access to financing, wartime risks, and the need to digitalize management processes. The directions of state policy for stimulating integration processes, developing cooperation, and supporting small and medium-sized businesses are summarized. The results of the study show that integration mechanisms are a key factor in strengthening the production potential of agricultural enterprises, thereby enhancing their financial stability and competitiveness at the national and international levels. The conclusions obtained can be used to improve capital management strategies, develop investment programs, and build an effective model for the development of Ukraine’s agricultural sector. In conditions of military operations, disruption of logistics chains, and rising production costs, integration mechanisms allow enterprises to maintain stability and realize economies of scale. The problem’s relevance also stems from the need to adapt Ukrainian agribusiness to European standards for sustainable development, the digitalization of production processes, and the expansion of participation in global value chains.